2007
DOI: 10.2353/ajpath.2007.070021
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles of Human Atherosclerotic Plaques Enhance the Shedding of the Tumor Necrosis Factor-α Converting Enzyme/ADAM17 Substrates, Tumor Necrosis Factor and Tumor Necrosis Factor Receptor-1

Abstract: Human atherosclerotic plaques express the metalloprotease tumor necrosis factor (TNF)-␣ converting enzyme (TACE/ADAM-17), which cleaves several transmembrane proteins including TNF and its receptors (TNFR-1 and TNFR-2). Plaques also harbor submicron vesicles (microparticles, MPs) released from plasma membranes after cell activation or apoptosis. We sought to examine whether TACE/ADAM17 is present on human plaque MPs and whether these MPs would affect TNF and TNFR-1 cellular shedding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 52 publications
2
86
0
3
Order By: Relevance
“…Patients with active AAV displayed enriched numbers of endothelial microparticles in their 43 and Canault and colleagues showed that ADAM17-containing microparticles of atherosclerotic plaques are partly of endothelial origin. 44 On the other hand, expression of ADAM17 is increased in activated leukocytes, and release of neutrophil microparticles is also strongly enhanced in AAV. 45,46 Moreover, expression of ADAM17, but not of ADAM10, is strongly enhanced in blood cells of patients with active AAV.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with active AAV displayed enriched numbers of endothelial microparticles in their 43 and Canault and colleagues showed that ADAM17-containing microparticles of atherosclerotic plaques are partly of endothelial origin. 44 On the other hand, expression of ADAM17 is increased in activated leukocytes, and release of neutrophil microparticles is also strongly enhanced in AAV. 45,46 Moreover, expression of ADAM17, but not of ADAM10, is strongly enhanced in blood cells of patients with active AAV.…”
Section: Discussionmentioning
confidence: 99%
“…8 When sequestered within the atheromatous plaque, microparticles disturb the inflammatory balance by exposing active tumor necrosis factor-alpha converting enzyme (TACE)/A Disintegrin And Metalloproteinase domain-17 (ADAM 17) that cleaves tumor necrosis factor (TNF) and its receptors. 9 Indeed, TACE + -microparticles are able to stimulate the release of proinflammatory TNF-α by endothelial cells.…”
Section: Pro-inflammatory Effects Of Microparticles On Endothelial Cementioning
confidence: 99%
“…13 TACE + -microparticles from the plaque were shown to promote the shedding of EPCR from endothelial cells, constituting another mechanism by which they contribute to enhanced in situ thrombogenicity. 9 Indeed, the loss of EPCR from the endothelial cell surface would impede the binding of activated protein C (APC). Endothelial microparticles themselves are part of the amplification loop leading to enhanced in situ thrombogenicity.…”
Section: Prothrombotic Potential Of Microparticles On Endothelial Cellsmentioning
confidence: 99%
“…Des facteurs épigénétiques et liés au sexe pourraient rendre compte de ces différences. Nos propres résultats montrent, chez la souris mâle génétiquement prédisposée à l'athérosclérose (apoE -/-) et chez l'homme, qu'ADAM17 est exprimée dans les lésions d'athérosclérose ( Figure 4) où les macrophages et les microparticules portent cette activité [28,29]. Ces données sont à rapprocher de celles que nous avons obtenues chez des souris mâles apoE -/-exprimant une forme mutée non clivable du tmTNF.…”
Section: Adam17 Dans L'obésité Et La Résistance à L'insulineunclassified